2023
DOI: 10.1007/s10549-023-06872-9
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of immunohistochemistry for predictive and prognostic factors in breast cancer between biopsy and surgical excision: a single-centre experience and review of the literature

Abstract: Purpose Accurate evaluation of breast cancer on bioptic samples is of fundamental importance to guide therapeutic decisions, especially in the neoadjuvant or metastatic setting. We aimed to assess concordance for oestrogen receptor (ER), progesterone receptor (PR), c-erbB2/HER2 and Ki-67. We also reviewed the current literature to evaluate our results in the context of the data available at present. Methods We included patients who underwent both biopsy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Previous studies have consistently indicated that PR expression shows lower agreement than ER expression in assessing inter-observer variability [ 40 , 41 ]. PR is a target gene regulated by estrogen and naturally displays greater homogeneity in normal breast tissues and tumors [ 22 , 42 ]. Intermediate biomarker expression categories are less reproducible than categories at the extremes [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have consistently indicated that PR expression shows lower agreement than ER expression in assessing inter-observer variability [ 40 , 41 ]. PR is a target gene regulated by estrogen and naturally displays greater homogeneity in normal breast tissues and tumors [ 22 , 42 ]. Intermediate biomarker expression categories are less reproducible than categories at the extremes [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…This process informs critical treatment decisions regarding potential neoadjuvant therapy before surgical interventions. In instances of complete pathological responses, the biopsy sample represents the sole remains of the available tumor [ 22 ]. Additionally, CNB samples are preferred over excision for biomarker testing because this approach helps to prevent many fixation problems [ 3 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry (IHC) is an established laboratory method for evaluating the presence of antigens that is widely used in breast cancer and is pivotal for tailoring systemic treatments (e.g., the human epidermal growth factor receptor 2—HER2) [ 10 ]. Moreover, IHC is significantly less expensive and laborious than gene expression and has been evaluated in several studies as a surrogate marker of established intrinsic genomic-based subtyping assays, as summarized in Table 1 [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this primary method is invasive, time-consuming, and nonrepeatable. The inherent heterogeneity of BC results in a concordance rate between CNB and excision specimen, with a substantial variation ranging from 59-88% (5,6). Additionally, the inability of the traditional approach to dynamically evaluate Ki-67 changes during neoadjuvant therapy highlights its limitations (7).…”
Section: Introductionmentioning
confidence: 99%